DAMPAK PENGGUNAAN TEKNOLOGI COMBINE HARVESTERTERHADAP PERUBAHAN SOSIAL EKONOMI PETANI PADI DESA PADANG KALUA KECAMATAN LAMASI KABUPATEN LUWU - -, Rusida (Jurnal Ilmiah Ecosystem, 2019)
This study aims to determine the socio-economic conditions of rice farmers before and after using Combine Harvester, where the socio-economic conditions in question are changes in labor aspects and changes in the harvest costs of rice farmers before and after using Combine Harvester. The population in this study were all rice farmers who used Combine Harvester in Padang Kalua Village, Lamasi District, Luwu Regency. The research sample was chosen by simple random sampling. Descriptive data analysis with a table of labor comparison and harvest costs.The results of the study show that the use of Combine Harvester technology can increase the income of rice farmers due to cheaper harvest costs. but on the other hand the use of Combine Harvster has an impact on the reduction in employment that affects the income of farm workers and the loss of additional income for farmers who have limited land.